Small Projects as Winners in the Organizational Learning Network - Sihvonen, Mika; Sipilä, Miikka (Proceedings of the International Conference on Networked Learning, 2014)
In this paper we argue that small development projects can be seen as the key actors in a large formal network of projects. The reason for this study were the observations made during the joint seminars and face-to-face meetings held for the overarching project network. The small projects or small teams of participatory projects remarked that learning experiences on those occasions were versatile and that there were a lot of possibilities for collaboration with other projects. At the same time, the people in the large projects considered themselves as information providers rather than as actual learners. The study focuses on the network of projects in a large national ESF development programme. One of the main goals of the development programme was to achieve a proper level of information sharing between its projects. The programme supervisors envisioned that, since all the projects had the same the target group of adult citizens, there had to be information to share during the programme’s run. In the right circumstances that could lead to organizational learning experiences and a sense of community. This research was conducted using a mixed approach involving qualitative and quantitative methods. The data was collected from an online survey and an interview round covering all development projects. Even though the resources for networking are usually limited in a small project or a project team, the dynamics and flexibility of small actors make information sharing easier. Small teams can implement learnt practices more easily, because there is no large scale sub-network to consider. A large project tends to work as an isolated unit and for each of its participatory projects the need of networking with their peer projects is lower. In this research learning is aimed at good or promising practices, which can be seen as artefacts that are disseminated and developed by the participating projects. As a conclusion we suggest that the teams or projects in a network should be equal in size if the network requires interaction for information sharing and learning. A large, network-type project could also participate, however it would need personnel who are in charge of information sharing.